Seeds - handle with care - Chin, H. F. (1979)
Seed is the most important input in crop production. Its quality determines succes or failure of a crop. A viable seed is an embryonic plant, it is fragile and has to be handled with great care. The quality of seeds has many facets, the more important factors also affect and contribute to seed quality. In this paper the biological, morphological and physical properties of some seeds are described. These characteristics require special considerations by all who handle seeds. The properties and requirements of seeds are different. For example, the orthodox and the recalcitrant seeds behave very differently. This is highlighted in the storage of maize (zea mays) and rambutan (Nephelium lappaceum) seeds where moisture and temperature are the most critical factors. Many contaminants such as poisonous seeds, noxious weed seeds, inert matter and other crop seeds are present in freshly harvested seed lots. These have to be carefully removed by machines before storage and planting. Mechanical injury is the main during the numerous mechanical operations from harvest to final bagging. A good knowledge of the biology and physical properties of seeds is not only useful but essential in seed processing, storage and planting.